The Achilles Heel of Whistleblowing Protection - Krambia-Kapardis, Maria; Papageorgiou, Andriani (My University, 2016)
In 1777, before the passage of the Bill of Rights, 10 sailors and marines blew the whistle on fraud and misconduct harmful to the United States. The Founding Fathers unanimously supported the whistleblowers and provided them with monetary assistance for reasonable legal expenses necessary to prevent retaliation. In an effort to demonstrate their full support, the members of the Continental Congress unanimously enacted the first whistleblower legislation in the United States that read: ‘It is the duty of all persons in the service of the United States, as well as all other inhabitants thereof, to give the earliest information to Congress or any other proper authority of any misconduct, frauds or misdemeanors committed by any persons in the service of these states, which may come to their knowledge.